Different recovery patterns of CMV-specific and WT1-specific T cells in patients with acute myeloid leukemia undergoing allogeneic hematopoietic cell transplantation: Impact of CMV infection and leukemia relapse - Luo, Xiao-Hua; Poiret, Thomas; Liu, Zhenjiang; Meng, Qingda; Nagchowdhury, Anurupa; Ljungman, Per (Frontiers in Immunology, 2023)
In allogeneic hematopoietic cell transplantation (allo-HSCT), both virus-specific T cells and leukemia-specific T cells need to be reconstituted to protect patients from virus infections and primary disease relapse. Cytomegalovirus (CMV) infection remains an important cause of morbidity and mortality after allo-HSCT. Emerging data indicate that CMV reactivation is associated with reduced risk of leukemia relapse in patients with acute myeloid leukemia (AML) undergoing allo-HSCT. In a cohort of 24 WT1+ AML patients during the first year following HSCT, CMV specific CD8+ T cells (CMV-CTL) reconstituted much faster than WT1-specific CD8+ T cell (WT1-CTL) after allo-SCT. Moreover, CMV-CTL expressed lower levels of exhaustion markers and were more functional as identified by production of IFN-γ / TNF-α and expression of Eomes/ T-bet. Interestingly, our patients with CMV reactivation presented higher frequency of CMV-CTL, lower levels of Eomes+T-bet- and higher levels of Eomes+T-bet+ expression in response to WT1 and CMV pp65 antigen during the first year after transplantation as compared to patients without CMV reactivation. Kinetics of CMV-CTL and WT1-CTL after transplantation might be associated with measurable residual disease and later leukemia relapse. Our results support that CMV reactivation, aside from the CMV-CTL reconstitution, could influence WT1-CTL reconstitution after allo-HSCT, thus potentially contributing to the remission/relapse of AML.